Evaluation of superficial femoral artery-lesions after percutaneous transluminal angioplasty: Color-coded summation images vs. monochromatic digital subtraction angiography - Augustin, Anne Marie; Thein, Irina; Rickert, Nicole; Klink, Thorsten; Bley, Thorsten Alexander; Kickuth, Ralph (BMC Medical Imaging, 2020)
Background: Percutaneous transluminal angioplasty (PTA) is increasingly requested in the therapy of peripheral arterial occlusive disease. The evaluation of the technical result after balloon angioplasty with regard to bailout stenting is highly dependent on the operatorś subjective assessment and mainly based on the monochromatic digital subtraction angiography (DSA) images. The aim of this study was to compare color-coded single image as a novel diagnostic tool with monochromatic DSA for the analysis of flow limitation and need for stent implantation after PTA of superficial femoral artery (SFA) stenoses. Methods: During a period of 18 months, 213 SFA lesions were treated by PTA with a standard balloon in 170 patients, resulting in a total of 193 endovascular procedures. The median age of the patients was 77 years (range, 35-96 years). Median length of the treated lesions was 10.5 cm (range, 1.0-50 cm). Three interventional radiologists retrospectively evaluated the results of balloon angioplasty with monochromatic as well as post-processed color-coded DSA images for flow limitations to decide if subsequent stent implantation was necessary. Consensus reading of two experienced interventional radiologists 2 months after the initial review served as reference standard to perform a receiver operating characteristics (ROC) analysis. Results: ROC analysis for readers A, B and C showed area under the curve (AUC) values of 0.797, 0.865 and 0.804 for color-coded DSA and AUC values of 0.792, 0.843 and 0.872 for monochromatic DSA: a significant advantage of color-coded over conventional monochromatic DSA was not found for readers A and B (p > 0.05). Results of reader C were significantly better in the assessment of monochromatic images (p = 0.023). Diagnostic confidence using color-coded images was slightly higher than in monochromatic images (κ = 0.486 vs. κ = 0.459). Conclusions: In this study, color coded DSA did not reveal to be superior to conventional monochromatic DSA when evaluating results of PTA and when deciding whether stent implantation is necessary or not. This technology, however, requires further experiences with special regard to homogeneously trained radiologists and to the time requirement.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Angiography; Angioplasty; Diagnostic imaging; Digital subtraction angiography; Endovascular procedures; Imaging analysis; Imaging postprocessing; Interventional radiology; Parametric color-coding; Peripheral arterial occlusive disease; Vascular imaging